Simulation and characterization of multi-phase flow and particle transport in porous media - Serrenho, Ana (2012)
The study of multiphase flow through porous structures is of considerable importance in many fields of science and technology. This paper analyzes numerically low and medium Reynold snumber flows in a cavity filled with porous materials and with a stagnant zone. Simulations were carried out with both a single-phase and two-phase flows. The transport of solid particles through the porous structure is also analyzed. This study covers Reynolds numbers ranging from 0.1 to 10 and Peclet numbers ranging from 0.5 to 10^5.